Preliminary phytochemical evaluation and vitamin C content of tolidus (hornstedtia havilandii (K. Schum) K. Schum) from Sabah / Nur Syafiqah Martang ... [et al] - Martang, Nur Syafiqah; Majito, Nadia; Jasnie, Farnidah; Wai, Lo Chor (Universiti Teknologi MARA, Sabah, 2020)
Most of the plants in the ginger family Zingeberaceae are well-known for their medicinal properties. However, the genus Hornstedtia found in Sabah is less reported. This research aims to investigate the phytochemical constituent and vitamin C content of a fruit, locally known as the Tolidus fruit in Sabah. The dried fruit sample was extracted using three solvents which were water, ethanol and methanol. The phytochemical constituents were determined using standard Colour Test for the presence of alkaloid, flavonoid, saponin and tannin. Then, the content of Vitamin C was determined using the standard Colorimetric Titration and ascorbic acid as standard. The phytochemical evaluation revealed that all three targeted constituents were present in all extracts except for the alkaloid. The vitamin C content was determined in both dried and fresh sample of fruits, where 52.84 mg was quantified in the fresh fruit aqueous extract and 23.93 mg in the dried fruit aqueous extract respectively. These results are comparable to the content of vitamin C in orange and lime fruits. The phytochemical evaluation and vitamin C content of Tolidus suggested the potential of this underutilised fruit to be the natural and affordable source of vitamin C. Additionally, may protect the body against harmful free radicals. However, further analysis is needed to determine other constructive natural contents and evaluate the efficacy of this fruit as a natural source of antioxidant.